Heparin-induced thrombocytopenia associated with acute liver graft failure. (27th November 2012) - Pannicke, Nadine; Pollok, Joerg-Matthias; Kluge, Stefan; Petzoldt, Martin
Abstract : An orthotopic liver transplantation (OLT) is of a proven benefit in an acute liver failure (ALF). Heparin-induced thrombocytopenia (HIT) is strongly associated with thromboembolic complications. We present the case of a 56-year-old patient who underwent an OLT owing to an ALF of unknown aetiology. HIT type II with consecutive hepatic and portal vein thrombosis caused progressive graft failure. Total hepatectomy and porto-caval shunt were performed to reduce the toxic effects of liver cell necrosis such as multiorgan failure involving the respiratory, renal and cardiovascular systems. A suitable liver graft was allocated after an anhepatic bridging period of 56 h. Specific complications due to end-stage liver failure—such as acidosis, coagulopathy, decrease of vascular resistance, cerebral oedema, myocardial infarction and right heart failure—were treated. Following a re-OLT, the patient made a complete recovery. We present a rare case of HIT-associated early liver graft failure followed by a prolonged anhepatic phase and finally a successful re-OLT.